Pendataan Basis Data Perumahan Berbasis Geospasial untuk Mendukung Peningkatan Kualitas Permukiman di Kelurahan Duri Selatan, DKI Jakarta - Anggit Putri; Mohammad Ischak; Ulfa Fatmasari Faisal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
High-density urban settlements face various challenges, including limited space, poor housing quality, and the lack of open spaces, which require accurate and integrated data to support effective planning. Kelurahan Duri Selatan, DKI Jakarta Province, is characterized by dense settlements and the presence of substandard housing conditions. This community service activity aims to develop a geospatial-based housing database using a by name by address approach to support the improvement of settlement quality. The methods applied include field surveys through direct observation, household interviews, and structured questionnaires, supported by spatial and non-spatial data collection using the Field Maps application. Data validation was conducted through a door-to-door approach and photographic documentation of housing conditions. The results indicate that Kelurahan Duri Selatan has a very high level of settlement density, limited availability of green open space, and the persistence of housing units with inadequate living conditions. Geospatial-based data collection using a Geographic Information System enables detailed and measurable identification of housing and environmental issues. In conclusion, geospatial-based housing data collection provides a strong technical foundation for settlement quality improvement planning and supports more targeted and sustainable decision-making at the local level.